A Review on Graphene Quantum Dots for Electrochemical Detection of Emerging Pollutants - Durodola, Solomon S.; Adekunle, Abolanle S.; Olasunkanmi, Lukman O.; Oyekunle, John A. O.; Ore, Odunayo T.; Oluwafemi, Samuel O. (Journal of fluorescence, 2022)
Graphene quantum dots which are known as zero-dimensional materials are gaining increasing attention from researchers all over the world. This is predicated upon their relatively unique chemiluminescent, fluorescent, electrochemiluminescent, and electronic properties. The precise mechanism of electrochemiluminescence continues to be a subject of debate in the research world, and this is important in identifying synthetic pathways for graphene quantum dots. Heavy metals and other emerging pollutants are global health and environmental concerns. Several studies have reported the sensitivity and limit of detection of graphene quantum dots up to the nano-, pico-, and femto- levels when used as sensors. This review seeks to bridge information gaps on the reported electrochemiluminescence chemosensors for emerging pollutants using graphene quantum dots under the sub-headings, synthesis, characterization, electrochemiluminescence chemosensor detection, and comparison with other detection methods.